Optimalisasi Digital Marketing Untuk Meningkatkan Omzet Usaha Mikro Dan Kecil Di Wringinanom Ponorogo - Kasanah, Nur; Elysa Septiana; Lia Alfi Karomah; Melfi Mutia Arifin; Muhammad Pandu Bagaskara; Munifah Rahmawati (Institut Agama Islam Negeri Ponorogo, 2022)
This community service activity aims to find alternative efforts in increasing the sales turnover of micro and small businesses in Wringinanom Village, Sambit District, Ponorogo Regency, which has many micro-businesses. This study uses the ABCD (Asset Based Community-Driven Development), which approaches the steps of inculturation, discovery, design, define, and reflection. Efforts are being made to optimize sales turnover through digital marketing by training on creating and maintaining accounts in Google Business and social media. The evaluation results show that digital marketing helps increase the sales turnover of micro-businesses in Wringianom Ponorogo.